Plasticity of Human CD4 T Cell Subsets - Geginat, Jens; Paroni, Moira; Maglie, Stefano; Alfen, Johanna Sophie; Kastirr, Ilko; Gruarin, Paola; De Simone, Marco; Pagani, Massimiliano; Abrignani, Sergio (Frontiers in Immunology, 2014)
Human beings are exposed to a variety of different pathogens, which induce tailored immune responses and consequently generate highly diverse populations of pathogen-specific T cells. CD4+ T cells have a central role in adaptive immunity, since they provide essential help for both cytotoxic T cell- and antibody-mediated responses. In addition, CD4+ regulatory T cells are required to maintain self-tolerance and to inhibit immune responses that could damage the host. Initially, two subsets of CD4+ helper T cells were identified that secrete characteristic effector cytokines and mediate responses against different types of pathogens, i. e. IFN-γ secreting Th1 cells that fight intracellular pathogens, and IL-4 producing Th2 cells that target extracellular parasites. It is now well established that this dichotomy is insufficient to describe the complexity of CD4+ T cell differentiation, and in particular the human CD4 compartment contains a myriad of T cell subsets with characteristic capacities to produce cytokines and to home to involved tissues. Moreover, it has become increasingly clear that these T cell subsets are not all terminally differentiated cells, but that the majority is plastic and in particular central memory T cells can acquire different properties and functions in secondary immune responses. In addition, there is compelling evidence that helper T cells can acquire regulatory functions upon chronic stimulation in inflamed tissues. The plasticity of antigen-experienced human T cell subsets is highly relevant for translational medicine, since it opens new perspectives for immune-modulatory therapies for chronic infections, autoimmune diseases and cancer.